Bounding Attachment Dan Tingkat Stress Ibu Postpartum - Yuliana Katoda; Lastri Mei Winarni; Isna Wanufika; H.A.Y.G Wibisono (Jurnal Kesehatan, 2020)
ABSTRACT Background: The result of bounding attachment researched which have been done about the frequency of bounding attachment from thirty five (53) respondents, that is, bounding attachment of 27 respondents (50,9%) are good and 12 respondents (22,6%) are deficient. Based on the researched from thirty five (53) respondents about the distribution of stressful level in postpartum mothers, that is, 22 respondents (41,5%) are not stressful and 15 respondents (28,3%) are very stressful. Research Objectives: The relationship of bounding attachment with stressful level in postpartum mothers. Research Methods: The researched methods are using for this researched that is quantitative analysis in descriptive correlation methods with total sampling are thirty five (53) respondents. Research Results: Based on chi-quare test and the statistic p-value are 0,020, the results shown that p-value score in the relationship of bounding attachment with the stressful level for postpartum mothers are <0,05. Then there is relationship of bounding attachment with the stressful level for postpartum mothers. Conclusions and recommendations: The researched result shown that there is a significant relationship between bounding attachment with the stressful level for postpartum mothers at RW. 05 Pondok Rejeki, Kel. Kota Baru, Kec. Pasar Kemis, Kab. Tangerang, particularly recommendations are for postpartum mothers to motivate their self to do bounding attachment while having their baby birth.